Carnitine metabolism and biosynthesis in the yeast Saccharomyces cerevisiae - Franken, Jaco (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Science) (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2009.